Flood risk management and real-estate prices: between prevention and “crowding out” effect - Dachary-Bernard, Jeanne (Frontiers in Environmental Economics, 2025)
Adapting to climate change is a key challenge for metropolis, and it partly deals with population location and flood risk management. The objective of this article is to understand the way flood risk is actually taken into account in residential choices. To this end, we measure how flood risk influences property prices and in particular, we target two specific flood management public instruments: the flood risk prevention plan (PPRI) and the public insurance mechanism (CatNat). We applied the hedonic price method over the period 2011–2016 to the French metropolitan area of Bordeaux, extended to include its neighboring estuarine municipalities. We show that flood risk zoning produces an expected significant deflating effect on prices whereas the CatNat system's insurance mechanism would appear to have a perverse effect. These results highlight an interesting crowding-out effect on the residential market that we finally discuss.